Analysis of metabolomics and transcriptomics data to assess interactions in microalgal co-culture of Skeletonema marinoi and Prymnesium parvum - Mahnoor Zulfiqar; Anne-Susann Abel; Emanuel Barth; Kristy Syhapanha; Remington Xavier Poulin; Sassrika Nethmini Costa Warnakulasuriya Dehiwalage; Georg Pohnert; Christoph Steinbeck; Kristian Peters; Maria Sorokina (PLoS ONE, 2025)
In marine ecosystems, microbial communities often interact using specialised metabolites, which play a central role in shaping the dynamics of the ecological networks and maintaining the balance of the ecosystem. With metabolomics and transcriptomics analyses, this study explores the interactions between two marine microalgae, Skeletonema marinoi and Prymnesium parvum, grown in mono-cultures and non-contact co-cultures. As a growth indicator, the photosynthetic potential, measured via fluorescence, suggested chemical interaction between S. marinoi and P. parvum. Using Liquid Chromatography-Mass Spectrometry (LC-MS) data, we identified 346 and 521 differentially produced features in the endo- and exometabolome of S. marinoi and P. parvum, respectively. Despite limited tandem mass spectrometry data (MS2) for these features, we structurally annotated 14 compounds, most of which were previously under-studied specialised metabolites. Differential gene expression analysis was then performed on the transcriptomes of the microalgae, which uncovered differentially expressed genes involved in energy metabolism and cellular repair for both species. These metabolic changes depict the adaptation of both species in the co-culture. However, further data acquisition and investigation will be necessary to confirm the type of interaction and the underlying mechanisms.